Friction in Oil-Lubricated Rolling–Sliding Contacts with Technical and High-Performance Thermoplastics - Ferdinand Schmid; Thomas Lohner; Karsten Stahl (Lubricants)
Thermoplastics show great potential due to their lightweight design, low-noise operation, and cost-effective manufacturing. Oil lubrication allows for their usage in high-power-transmission applications, such as gears. The current design guidelines for thermoplastic gears lack reliable estimates for the coefficient of friction of oil-lubricated rolling–sliding contacts. This work characterizes the friction of elastohydrodynamic rolling–sliding contacts with technical and high-performance thermoplastics with oil lubrication. The influence of polyoxymethylene (POM), polyamide 46 (PA46), polyamide 12 (PA12), and polyetheretherketone (PEEK), as well as mineral oil (MIN), polyalphaolefin (PAO), and water-containing polyalkylene glycol (PAGW), was studied. Experiments were carried out on a ball-on-disk tribometer, considering different loads, speeds, temperatures, and surface roughness. The results show that, for fluid film lubrication, there is very low friction in the superlubricity regime, with a coefficient of friction lower than 0.01. Both sliding and rolling friction account for a significant portion of the total friction, depending on the contact configuration and operating conditions. In the mixed to boundary lubrication regime, the sliding friction depends on the thermoplastic and rises sharply, thus increasing the total friction.